Activation of a Silent Polyketide Synthase SlPKS4 Encoding the C7-Methylated Isocoumarin in a Marine-Derived Fungus Simplicillium lamellicola HDN13-430 - Jing Yu; Xiaolin Liu; Chuanteng Ma; Chen Li; Yuhan Zhang; Qian Che; Guojian Zhang; Tianjiao Zhu; Dehai Li (Marine Drugs, 2023)
Coumarins, isocoumarins and their derivatives are polyketides abundant in fungal metabolites. Although they were first discovered over 50 years ago, the biosynthetic process is still not entirely understood. Herein, we report the activation of a silent nonreducing polyketide synthase that encodes a C7-methylated isocoumarin, similanpyrone B (1), in a marine-derived fungus Simplicillium lamellicola HDN13-430 by heterologous expression. Feeding studies revealed the host enzymes can change 1 into its hydroxylated derivatives pestapyrone A (2). Compounds 1 and 2 showed moderate radical scavenging activities with ED50 values of 67.4 µM and 104.2 µM. Our discovery fills the gap in the enzymatic elucidation of naturally occurring C7-methylated isocoumarin derivatives.